Teaching in the digital age for preschool and kindergarten : enhancing curriculum with technology - Puerling, Brian (St. Paul, MN : Redleaf Press, 2018)
"Make well-informed decisions about when, how, and why to use technology with young children. Technology is moving faster than teachers and children can keep up with. Teaching in the Digital Age guides teachers of preschool and kindergarten aged children toward integrating technology across the curriculum so it can have an authentic, meaningful, and developmentally appropriate impact on children's exploration and learning. Full of strategies and stories, photographs and videos, this book provides a clear picture of how to integrate technology that will expand awareness and ignite the teacher's excitement. Full of strategies, personal stories of integrating technology into the classroom, photographs, videos, and web resources, this book will help teachers make well-informed decisions about when, how, and why they use technology and media with young children in preschool and kindergarten. Organized by discipline--including science, math, literacy, art, social studies, health and safety, physical education, and music it will motivate teachers to dig deeper into each area to see the many ways technology and digital media can support and strengthen children's learning, as well as documentation and assessment" -- From the publisher.
Introduction : Goals and intentions of this book -- An integrated approach to curriculum -- Science -- Mathematics -- Literacy (language, reading, and writing) -- Art -- Music -- Social studies -- Health and safety -- Physical education -- Conclusion : Moving forward -- Appendix : Mobile device applications.
Includes bibliographical references and index.
Keywords: Education, Preschool -- Computer-assisted instruction; Education, Preschool -- Curricula; Education -- Effect of technological innovations on; Educational technology